2018
DOI: 10.2147/ppa.s159306
|View full text |Cite
|
Sign up to set email alerts
|

Living with cystic fibrosis – a qualitative study of a life coaching intervention

Abstract: BackgroundCystic fibrosis (CF) is a chronic, life-shortening disease with a significant treatment burden. To support young adults with CF in their everyday life, we previously conducted a life coaching feasibility trial (published elsewhere). The aim of the current study was to explore how life coaching was experienced by study participants within the context of their lives with CF.MethodsA qualitative study using individual interviews. Respondents (n=14) were recruited from the intervention group after partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 39 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…Figure 1 provides a PRISMA flow diagram indicating the inclusion and exclusion of articles at each stage of the screening process. The included papers were published between 2011 and 2019, from Australia (Eassey, Reddel, Ryan, & Smith, 2019 ), the Netherlands (Knudsen et al, 2018 ), South Africa (Murphy, Chuma, Mathews, Steyn, & Levitt, 2015 ) and the United States (Bhattacharya, 2012 ; Bingham & Meyer, 2011 ; Bingham, Crane, & Manning, 2017 ). The included papers described people’s experiences of living with: cystic fibrosis (Bingham & Meyer, 2011 ; Knudsen et al, 2018 ), asthma (Bingham et al, 2017 ; Eassey et al, 2019 ), diabetes (Bhattacharya, 2012 ) and hypertension (Murphy et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 1 provides a PRISMA flow diagram indicating the inclusion and exclusion of articles at each stage of the screening process. The included papers were published between 2011 and 2019, from Australia (Eassey, Reddel, Ryan, & Smith, 2019 ), the Netherlands (Knudsen et al, 2018 ), South Africa (Murphy, Chuma, Mathews, Steyn, & Levitt, 2015 ) and the United States (Bhattacharya, 2012 ; Bingham & Meyer, 2011 ; Bingham, Crane, & Manning, 2017 ). The included papers described people’s experiences of living with: cystic fibrosis (Bingham & Meyer, 2011 ; Knudsen et al, 2018 ), asthma (Bingham et al, 2017 ; Eassey et al, 2019 ), diabetes (Bhattacharya, 2012 ) and hypertension (Murphy et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies did not focus on what matters to people in their everyday experiences of living with a chronic illness but rather more specifically on barriers to self-management (Bhattacharya, 2012 ; Bingham et al, 2017 ; Bingham & Meyer, 2011 ; Knudsen et al, 2018 ; Murphy et al, 2015 ). Of the six studies, four aimed to identify factors that could be used in subsequent intervention studies by focusing on the challenges to patients’ basic psychological needs (Bhattacharya, 2012 ; Bingham et al, 2017 ; Bingham & Meyer, 2011 ; Murphy et al, 2015 ), one study explored patient experiences of participating in a life coaching intervention (Knudsen et al, 2018 ) and one explored in depth the role of autonomy in experiences of living with a debilitating condition (Eassey et al, 2019 ). Five studies reported on all three of SDT’s basic psychological needs (autonomy, competence and relatedness) (Bhattacharya, 2012 ; Bingham et al, 2017 ; Bingham & Meyer, 2011 ; Knudsen et al, 2018 ; Murphy et al, 2015 ) and one study analysed and interpreted one of the needs (autonomy) in depth using people’s narratives (Eassey et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations